(untitled) (REMUNOM, 2025)
Introduction: The main objective of the Adequacy of the Oral Environment (AMB) is to reduce and/or eliminate bacterial microorganisms present in the oral cavity through its stages, preventing the appearance of new carious lesions, balancing the oral environment. Objective: The present work proposes to present a discussion about AMB, through a literature review, addressing its stages, distinguishing it from Atraumatic Restorative Treatment, seeking to qualify AMB as a preventive treatment modality. Methods: This is a narrative review, supported by works related to the topic. Results: The discussion of the work allowed us to address the stages of adapting the environment, framing them in the daily routines of oral care. It was possible to present AMB by distinguishing it from Atraumatic Restorative Treatment and positioning it as a prevention measure and not health promotion as a proposal to be reflected on by the dental profession. Conclusion: It can be concluded that it is essential to provide active participation in the daily oral activities of patients assisted by their guardians, represented by shared construction of strategies aimed at controlling tooth decay. It is suggested that this attitude promotes independence and autonomy in adopting measures that can rebalance the oral environment, even in the AMB phase. Another aspect to be highlighted is linked to the proposal to classify AMB as a preventive treatment modality, since all measures adopted refer to the control of caries and/or periodontal disease.